TEACHERS’ PERCEPTION ON REFLECTIVE TEACHING IN TEACHING ENGLISH AS FOREIGN LANGUAGE - Aulia Rahmanita (Journal of English Education Program (JEEP), 2016)
This study reports the survey about teachers’ perception on reflective teaching in teaching English as foreign language at junior high school. Reflective teaching means looking at what teachers do in the classroom, thinking about why teachers do it, and thinking about if it works – a process of self-observation and self-evaluation. This study was aimed at finding out: What are teachers’ perception on reflective teaching in teaching English as foreign language. The writer used survey research as a method to investigate the problem. To get the data the writer distributed questionnaire, particularly close ended questionnaire to thirty teachers at eight junior high schools in Ciamis. The result show that teachers have known about nature of reflective teaching category and micro teaching category, but most of the teachers have lack of knowledge about peer mentoring and self evaluation, action research and professional development.